Marketing Strategy for Pawn Gold Products at Bank Syariah Indonesia Duri Branch Office - Syafri Dianto (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2019)
This research is motivated because by looking at the rapid developments that occur in Islamic banking, several financial institutions, especially Islamic banking, have begun to open sharia pawn products or also known as rahn. However, for now, financial institutions such as Islamic banking only accept pawned goods in the form of gold bars or bullion, gold jewelry or gold coins. This is due to the small value of the risk that will occur and the existence of the value of gold itself which remains stable and even tends to increase from year to year and is not affected by inflation.Regarding the need for marketing, it is unavoidable because of market developments and increasingly fierce competition. Marketing is not only needed by companies but is used by Islamic financial institutions such as Bank Syariah Indonesia Duri Branch Office in the development of their products, especially the Gold Pawn product.